2010
DOI: 10.2176/nmc.50.161
|View full text |Cite
|
Sign up to set email alerts
|

Extracranial Metastasis of Anaplastic Oligodendroglioma With 1p19q Loss of Heterozygosity -Case Report-

Abstract: We report a rare case of anaplastic oligodendroglioma with extracranial metastasis, showing 1p19q codeletion in both the brain tissue and the metastatic site. A 53-year-old man first presented with a left frontal tumor. The tumor was subtotally removed and irradiation was performed for the residual tumor and tumor bed. Two years after the initial treatment, several tumors appeared on his neck and one was resected. Histological examination revealed anaplastic oligodendroglioma, proved to be the same as the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Two potential mechanisms of systemic metastasis have been described: (1) scalp and/or regional lymph node involvement followed by distant spread, which was observed in patients with recurrent craniotomies, occurring years after the initial diagnosis; and (2) potential direct hematogenous spread to distant organs, occurring in the early period of tumor growth [10,16,17]. The data show that multiple occult metastases are observed and that the clinical prognosis is worse in the second group [7]. The frequency of extracranial metastasis of OG is lower than that of other glial tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two potential mechanisms of systemic metastasis have been described: (1) scalp and/or regional lymph node involvement followed by distant spread, which was observed in patients with recurrent craniotomies, occurring years after the initial diagnosis; and (2) potential direct hematogenous spread to distant organs, occurring in the early period of tumor growth [10,16,17]. The data show that multiple occult metastases are observed and that the clinical prognosis is worse in the second group [7]. The frequency of extracranial metastasis of OG is lower than that of other glial tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the relatively high incidence of multiple intraneural metastases by cerebrospinal fluid following leptomeningeal involvement, to date, less than 50 cases of systemic metastasis of OG have been reported in the literature [4,5,6,7,8]. However, the real incidence may be higher when autopsy cases are considered [7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Some researchers argue that the codeletion of chromosomes 1p/19q is specific to oligodendroglioma, and it has been proposed as a diagnostic marker for this tumour. 17,18 Other reports have, however, also documented the codeletion of chromosomes 1p/19q in 17% 19 or 24% 4 …”
Section: Atypical Evn: a Case Reportmentioning
confidence: 98%
“…Liwnicz and Rubinstein (2) reviewed 116 cases of extracranial metastases and found that the most common primary tumor was glioblastoma (41.4%), followed by medulloblastoma (26.7%), ependymoma (16.4%), astrocytoma (10.3%), and oligodendroglioma (5.25%). Oligodendroglioma is the least common type to metastasize and only~30 cases have been reported (3). Davis, in 1928, first described an extracranial metastasis of glioblastoma following craniotomy (4), whereas Rubinstin, in 1967, reported a case of glioblastoma with extracranial metastasis without craniotomy (3).…”
mentioning
confidence: 99%